The endocannabinoid system – current implications for drug development. (29th January 2021) - Fowler, C. J.
Abstract: In this review, the state of the art for compounds affecting the endocannabinoid (eCB) system is described with a focus on the treatment of pain. Amongst directly acting CB receptor ligands, clinical experience with ∆ 9 ‐tetrahydracannabinol and medical cannabis in chronic non‐cancer pain indicates that there are differences between the benefits perceived by patients and the at best modest effect seen in meta‐analyses of randomized controlled trials. The reason for this difference is not known but may involve differences in the type of patients that are recruited, the study conditions that are chosen and the degree to which biases such as reporting bias are operative. Other directly acting CB receptor ligands such as biased agonists and allosteric receptor modulators have not yet reached the clinic. Amongst indirectly acting compounds targeting the enzymes responsible for the synthesis and catabolism of the eCBs anandamide and 2‐arachidonoylglycerol, fatty acid amide hydrolase (FAAH) inhibitors have been investigated clinically but were per se not useful for the treatment of pain, although they may be useful for the treatment of post‐traumatic stress disorder and cannabis use disorder. Dual‐acting compounds targeting this enzyme and other targets such as cyclooxygenase‐2 or transient potential vanilloid receptor 1 may be a way forward for the treatment of pain. Abstract :